Handbook for Literacy Lesson Planning : Early-grade Classroom Activities for Teaching Children to Read - World Bank (Washington, DC, 2022)
This Handbook for Literacy Lesson Planning is designed to be used as a resource for education stakeholders seeking to design evidence-aligned early grade literacy programs. It describes the different subskills involved in learning to read, outlines best classroom practices for each subskill, and offers examples of high-quality classroom activities for each best practice.